Time- and temperature-dependent crosslinking behaviour of a silicone resin - Wolff, Friedrich; Kugler, Christoph; Münstedt, Helmut (Rheologica Acta, 2012)
The crosslinking behaviour of a silicone resin which is interesting from a technical point of view was investigated by means of rheology. In order to accelerate the crosslinking process, zinc acetylacetonate and aluminium acetylacetonate were applied as latent catalysts. The effect of the type of catalyst, its concentration, and the temperature on crosslinking was determined by isothermal dynamic-mechanical measurements. A radial gradient in crosslinking causes the gel point to be reached earlier at the outer edge of the sample in the rheometer. This radial gradient is averaged when measuring G′ and G''. Therefore, since the physically well-defined state of critical gelation (gel point) could not be obtained from the data, the time at which a distinct crosslinking state is reached was determined by the crossover of the moduli G′ and G''. For this distinguished point, the denotation gelation index GI is introduced. The gelation indices measured at different temperatures follow an Arrhenius-type relationship. Activation energies between 89 and 126 kJ/mol were determined. They were found to be dependent on the type of catalyst used but independent of its concentration. The activation energies of the crosslinking processes enable the calculation of the gelation index at temperatures not measured directly.
EAM Import::2019-03-12